2022
DOI: 10.1259/bjr.20220379
|View full text |Cite
|
Sign up to set email alerts
|

Role of interventional oncology in hepatocellular carcinoma: Future best practice beyond current guidelines

Abstract: Hepatocellular carcinoma is a leading cause of cancer-related deaths globally. Liver transplant remains the goal of curative treatment, but limited supply of organs decreases accessibility and prolongs waiting time to transplantation. Therefore, interventional oncology therapies have been used to treat the majority of HCC patients, including those awaiting transplant. The Barcelona Clinic Liver Cancer (BCLC) classification is the most widely used staging system in management of hepatocellular carcinoma (HCC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 113 publications
0
9
0
Order By: Relevance
“…In this context, a bridging therapy, such as transarterial radioembolization (TARE) before liver transplantation (LT), is applied. The effectiveness of locoregional, neoadjuvant therapies for this purpose has been demonstrated by several studies [ 5 , 6 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies directly comparing TARE with TACE found a higher disease control rate, significantly better overall and intrahepatic PFS, and better survival outcomes in the patients treated with TARE even with advanced disease [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a bridging therapy, such as transarterial radioembolization (TARE) before liver transplantation (LT), is applied. The effectiveness of locoregional, neoadjuvant therapies for this purpose has been demonstrated by several studies [ 5 , 6 , 11 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Studies directly comparing TARE with TACE found a higher disease control rate, significantly better overall and intrahepatic PFS, and better survival outcomes in the patients treated with TARE even with advanced disease [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BCLC system, which is widely accepted for HCC staging and the treatment selection (16), does not recommend hepatectomy for stage B disease patients. However, several studies have suggested that potentially curative treatments, such as resection, can be safe and effective for stage B disease patients (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…In current guidance, priority on the waiting list is made for patients with HCC who are on the waiting list for at least six months and are within the Milan Criteria (i.e., one lesion up to 5 cm or up to 3 lesions ≤ 3 cm with no features of macrovascular invasion or extrahepatic disease) [ 22 ]. Notably, in recent years, a number of centres have adopted criteria beyond the standard Milan criteria, such as those of the University of California, San Francisco (UCSF).…”
Section: Non-ablative Treatment Optionsmentioning
confidence: 99%